Regulations on land fund development according to the draft amended Law on Land and several assessments and suggestions for completion - Tran, Linh Huan; Pham, Thi Hong Tam; Nguyen, Thi Thao Uyen; Do, Thi Van (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
In order to develop the land fund and help the state be more proactive in allocating land, the Ministry of Natural Resources and Environment has proposed Chapter VIII on land fund development in the Draft amended Law on Land. Within the scope of this article, the focus is on analyzing and evaluating the limitations and inadequacies in the regulations on land fund development based on a comparison between the Draft amended Law on Land and the current Law on Land, thereby making some suggestions to improve legal provisions to establish a comprehensive and strict legal framework for land fund development activities in Vietnam today.